INTRA OPERATIVE COMPLICATIONS DURING VITRECTOMY PERFORMED BY POST GRADUATE RESIDENTS - Ur Rehman, Ashfaq; Attique, Usman; Jan, Sanaullah (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine intra operative complications during pars plana vitrectomy performed by vitreo retinal residents. Methodology: A hospital based case series study was carried out over a period of 6 months. Intra operative data of 62 patients who underwent vitrectomy by Vitreo Retina (VR) residents, who already held fellowship in ophthalmology, were collected. Demography, indications of vitrectomy and intra operative complications were recorded. The data were analyzed using SPSS version 20. Results: The most frequent intra operative complication was iatrogenic retinal break (27.41%), followed by capsular breach lens touch (22.58%). Vitreous cutter and light probes were the most frequent causes of these complications. Conclusion: Iatrogenic retinal break was the commonest complication encountered by residents during vitreoretinal surgery followed by lens touch.